The VISTA Variables in the Vía Láctea eXtended (VVVX) ESO public survey: Completion of the observations and legacy - Saito, R. K. (2024)
ontext. The ESO public survey VISTA Variables in the Vía Láctea (VVV) surveyed the inner Galactic bulge and the adjacent southern Galacticdisk from 2009 − 2015. Upon its conclusion, the complementary VVV eXtended (VVVX) survey has expanded both the temporal as well as spatialcoverage of the original VVV area, widening it from 562 to 1700 sq. deg., as well as providing additional epochs in JHKs filters from 2016 − 2023.Aims. With the completion of VVVX observations during the first semester of 2023, we present here the observing strategy, a description of dataquality and access, and the legacy of VVVX.Methods. VVVX took ∼ 2000 hours, covering about 4% of the sky in the bulge and southern disk. VVVX covered most of the gaps left betweenthe VVV and the VISTA Hemisphere Survey (VHS) areas and extended the VVV time baseline in the obscured regions affected by high extinctionand hence hidden from optical observations.Results. VVVX provides a deep JHKs catalogue of & 1.5 × 109 point sources, as well as a Ks band catalogue of ∼ 107 variable sources. Withinthe existing VVV area, we produced a 5D map of the surveyed region by combining positions, distances, and proper motions of well-understooddistance indicators such as red clump stars, RR Lyrae, and Cepheid variables.Conclusions. In March 2023 we successfully finished the VVVX survey observations that started in 2016, an accomplishment for ESO ParanalObservatory upon 4200 hours of observations for VVV+VVVX. The VVV+VVVX catalogues complement those from the Gaia mission at lowGalactic latitudes and provide spectroscopic targets for the forthcoming ESO high-multiplex spectrographs MOONS and 4MOST.